PERJUANGAN KESETARAAN GENDER, NILAI PENDIDIKAN KARAKTER DALAM NOVEL KENANGA KARYA OKA RUSMINI DAN RELEVANSINYA DALAM PEMBELAJARAN SASTRA DI PERGURUAN TINGGI - Tripungkasingtyas, Sri Yuniarti; Wardani, Nugraheni Eko; Sumarlam, Sumarlam (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This research aims to describing and explain : (1) structure novel Kenanga by Oka Rusmini; (2) gender inequity in the novel Kenanga by Oka Rusmini; (3) the struggle gender equality in the novel Kenanga; (4) value education responsibility in the novel Kenanga; and (5) relevance novel Kenanga as of matter learning literature in college. The research is describe qualitative by adopting feminism. The primary data sources in the form of novels Kenanga by Oka Rusmini and secondary data sources in the form informant, books, and journal. The technique collection data in this research using content analysis and interview. Validation data in this research using triangulation data sources and triangulation method. This research using a technique data analysis interactive model Miles and Hubermen. The research result show that: (1) structure novel Kenanga by Oka Rusmini covering theme, characterizations, plot, setting, and mandate; (2) Gender inequity in the novel Kenanga covering subordination, violence, workload, and labeling negative; (3) the struggle gender equality in the novels Kenanga covering field of education, field of job, field of public, field of family, and system caste/culture; (4) the educational value of the character in the novel Kenanga is value responsibility; and (5) the relevance novel Kenanga as of matter learning in college. This can be seen from syllabus feminist literary criticism with k.d students can understand criticism of feminism in a literary work and interviews with several informants and students.